Respuesta :
Step-by-step explanation:
7(x + 6) = 42
distributive property: a(b + c) = ab + ac
(7)(x) + (7)(6) = 42
7x + 42 = 42
subtraction property of equality (subtract 42 from both sides)
7x + 42 - 42 = 42 - 42
7x = 0
division property of equality (divide both sides by 7)
7x : 7 = 0 : 7
x = 0
Answer:
1. Distributive property: a(b + c) = a.b + a.c
2. Property of subtraction of equality
3. Property of division of equality
Step-by-step explanation:
The given equation is 7x + 42 = 42
7(x+6)=42 [Distributive property: a(b + c) = a.b + a.c]
7x+42=42 [Property of subtraction of equality]
Subtract 42 from both sides.
7x + 42 - 42 = 42 - 42
7x=0
Property of division of equality
Divide both sides by 7.
x=0